Răspuns :
a = b + c = 6
a = 3 + 3 = 6
a = 1 + 5 = 6
a = 5 + 1 = 6
a = 2 + 4 = 6
a = 4 + 2 = 6
a = 6 + 0 = 6
a = 0 + 6 = 6
Sper că te-am ajutat . Multă baftă ! :*
a = 3 + 3 = 6
a = 1 + 5 = 6
a = 5 + 1 = 6
a = 2 + 4 = 6
a = 4 + 2 = 6
a = 6 + 0 = 6
a = 0 + 6 = 6
Sper că te-am ajutat . Multă baftă ! :*
a=b+c=6 ⇒ mereu a va fi egal cu 6
6=0+6=a
6=1+5=a
6=2+4=a
6=3+3=a
mai apoi, se inversează, adică: 3+3; 4+2; 5+1; 6+0
Sper că ți-am fost de folos
6=0+6=a
6=1+5=a
6=2+4=a
6=3+3=a
mai apoi, se inversează, adică: 3+3; 4+2; 5+1; 6+0
Sper că ți-am fost de folos